The GOS4M Knowledge Hub: A web-based effectiveness evaluation platform in support of the Minamata Convention on Mercury. Issue 124 (October 2021) - De Simone, Francesco; D'Amore, Francesco; Bencardino, Mariantonia; Carbone, Francesco; Hedgecock, Ian M.; Sprovieri, Francesca; Cinnirella, Sergio; Pirrone, Nicola
Highlights: The GOS 4 M Knowledge Hub provides an interactive and user friendly experience to access state-of-the-art Hg modelling tools. GOS 4 M Knowledge Hub includes a CTM emulator, HERMES, for the short-term assessment of Hg emissions reduction policies. GOS 4 M Knowledge Hub is coupled with a biogeochemical model for a long-term assessment of Hg emissions reduction policies. GOS 4 M Knowledge Hub has been designed to house and deploy any number of different modelling components. GOS 4 M Knowledge Hub allows user to make policy scenario assessments in seconds, compared to days or weeks. Abstract: The Minamata Convention on Mercury was established to reduce the pressure on the environment caused by mercury by significantly reducing its emissions from anthropogenic activities. However, knowledge gaps still exist concerning emission inventories, emission factors and their integration in modelling frameworks. In addition, tools to facilitate communication between decision-makers and research groups providing measurement and modelling data are still scarce. This work presents the GOS 4 M Knowledge Hub, a public web application that provides an interactive and user friendly experience to access state-of-the-art modelling tools and data available in the literature. The Knowledge Hub currently integrates a Chemical Transport Model emulator, HERMES, coupled with a biogeochemical model, although it has been designed to house and deploy any number of different modelling components. Using the integrated dashboard, non-experts can perturb mercury releases from different anthropogenic emission sectors, simulating, for example, the application of Best Available Technologies, and then visualise in real-time the short- and long-term effects of the consequent reductions within a source-receptor framework. The dashboard also furnishes an estimate of the statistical significance of the changes in the model results. The analysis of a set of anthropogenic Hg emission reduction scenarios shows how an internationally coordinated effort would be necessary to achieve significant policy goals. It is important to note that the GOS 4 M Knowledge Hub yields the analysis presented here in a matter of seconds, compared to the days or weeks required by traditional modelling tools.